PENGARUH GAYA KEPEMIMPINAN MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. BANK KALBAR PUSAT PONTIANAK - admin, Desi Surya Pratiwi B11111046 (Jurnal Manajemen Update, 2016)
This study aims to determine the effect of leadership style, motivation and disciplinethe performance of employees at PT. Bank Kalbar Pusat Pontianak. PT. Bank Kalbar PusatPontianak raise funds engaged in customer deposits, lending and financing, as well asproviding other banking services by presenting a diverse range of products and services, bothconventional and shariaThis type of research is causal research and survey research. Data collectiontechniques by using primary data and secondary data. The data analysis technique used isthe technique of multiple linear regression analysis, processed using SPSS Version 16.Hypothesis testing is done by distributing questionnaires as many as 95 employees of PT.Bank Kalbar Pusat PontianakBased on the research results it is concluded that the partial leadership style variable,variable work discipline and motivation variables significantly influence the performance ofemployees at PT. Bank Kalbar Pusat PontianakKeywords: Style of Leadership, Motivation, Work Discipline and Performance